Synthesis, physico-chemical properties of 2-((4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazol-3-yl)thio)acetohyd-razides - A. A. Safonov (The State Expert Center of the Ministry of Health of Ukraine, 2018)
The value of the class of 1,2,4-triazole derivatives to create a low-toxic and highly active substances is huge. There are a lot of facts about the high biological activity among a number of substances. The 2-((4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazol-3-yl)thio)acetohydrazides derivatives causes of particular interest in this direction. The aim of the work was to synthesize 2-((4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazol-3-yl)thio)acetohydrazides and their derivatives, studying of their physico-chemical properties. 2-((4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazol-3-yl)thio)-N'-R-acetohydrazides were synthesized by of 2-((4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazol-3-yl)thio)acetohydrazides with aldehydes and ketones in the i-propanol with the addition of hydrochloric acid. The melting point was determined by an automatic device for determining the melting point OptiMelt Stanford Research Systems MPA100 (US). The elemental composition of compounds found in elemental analyzer Elementar Vario L cube (CHNS) (standard ‒ sulfonamides). Chromatography-mass spectral studies conducted on gas-liquid chromatograph Agilent 1260 Infinity HPLC with equipped mass spectrometer Agilent 6120, 1H-NMR-spectra were registered on spectrometer Mercury 400 A series of new 2-((4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazol-3-yl)thio)-N'-R-acetohydrazides derivatives were synthesized, R-2-chloro-6-fluorobenzylidene, 3-nitrobenzylidene, 4-hydroxybenzylidene, 2-nitrobenzylidene, 2,4-dimethylbenzylidene, 3,5-dimethoxybenzylidene, 3-bromo-4-fluorobenzylidene, 2,3-dimethoxybenzylidene, 2-bromobenzylidene, 2-fluorobenzylidene, 4-(dimethylamino)benzylidene, pyridin-2-ylmethylene, 5-nitrofuran-2-ylmethylene, 4-methoxybenzylidene, 2-hydroxybenzylidene, 4-methoxyphenyl)ethylidene, 1-(thiophen-2-yl)ethylidene. The structure of these compounds was established by modern physico-chemical analysis methods (elemental analysis, 1H-NMR spectroscopy). Individuality was proved by HPLC-MS.